Assessing the Achievement Testing Practices of Teachers in Junior High Schools in the Sissala East Municipality of Ghana - Zakariya, Jallu; Cobbinah, Andrews (European Scientific Journal, ESJ, 2021)
The study sought to find out whether Junior High School teachers in the Sissala East Municipality of Ghana follow the basic prescribed principles in the construction, administration and scoring of classroom achievement tests. A descriptive survey design was adopted for the study. The study employed multistage sampling techniques (purposive, stratified, and simple random sampling procedures) to select a sample of 248 teachers from the Sissala East Municipality. A questionnaire was used for the data collection and its reliability was 0.8. Data were analysed using frequencies, means, and standard deviation. The results showed that generally, Junior High Schools teachers in the Sissala East Municipality adhere to most principles of test construction and test administration but had little knowledge of the principles in the scoring test. It was recommended that more workshops and in-service training should be organized for teachers in Junior High Schools concerning their testing practices (i.e., construction, administration and scoring of tests).